Effect of Papaya Leaf Extract Gel (Carica papaya) on Incision Wound Healing in Rattus norvegicus - Iin Tri Marlinawati; Siti Nurhidayah; Sanarto Santoso; Yahya Irwanto (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
Carica papaya is one kind of herbal plant that can help the wound healing process. Scientifically, the leaves of papaya are proven to have anti-inflammatory effects. Flavonoid, alkaloid, tannin, and saponin compounds in papaya leaves have antimicrobial and antioxidant properties to accelerate the re-epithelization and cell migration needed for wound healing. This research aims to determine the effect of papaya leaf extract gel (Carica papaya) on the healing of incision wounds in Rattus norvegicus based on changes in wound morphology (signs of redness, edema, pus, granulation, moisture, and wound length). This research used female Rattus norvegicus aged 12-16 weeks weighing 180-200 grams, divided into five groups (NaCl 0,9%, povidone-iodine, papaya leaf extract gel with concentrations of 10%, 20%, and 30%). Incision wounds on the back of the rat with a length of 2 cm and depth of 1 cm. The normality test used the Shapiro-Wilk test, and the homogeneity test used the Levene test. The research data were not normally distributed nor homogeneous, so they were analyzed using the Kruskal Wallis and Mann-Whitney tests. The results showed that the extract of papaya leaves with concentrations of 10%, 20%, and 30% had significant differences in positive and negative control groups in the wound healing process with the differences in redness (p=0.038), granulation tissue (p=0.039), moistures (0,48), and wound length (p=0,049). It can be concluded that papaya leaf extract gel (Carica papaya) is effective in accelerating the healing process of incision wounds in Rattus norwegicus at concentrations of 10%, 20%, and 30%, so for further research, it is hoped that a histopathological examination can be carried out so that changes that occur in collagen, neutrophile cells, monocytes, and lymphocytes are seen.